Effects of autumn tillage with straw return on soil physical characteristics of corn fields in the eastern loess plateau - Fan, Yuchen; Yuan, Yaqi; Li, Tao; Lin, Wen; Tang, Xiwang; Liang, Gaimei; Li, Nana (Frontiers in Environmental Science, 2024)
The implementation of unsuitable tillage practices has the potential to disrupt the structure integrity of the ploughed layer, as well as to influence the physical parameters of the soil. The application of a reasonable tillage method has been demonstrated to result in an improvement in the physical quality of the soil. Three autumn tillage practices have been implemented at the Dongyang Experimental Station of Shanxi Agricultural University since 2016: no-tillage with straw mulch (NTS), autumn rotary tillage with straw incorporation (RTS), and autumn plough tillage with straw incorporation (PTS). The impact of autumn tillage practices on soil physical quality in the 0–30 cm profile of spring corn fields was evaluated following the corn harvest in 2018 and 2019. The results showed that compared to the NTS treatment, the application of RTS was found to have decreased significantly by 9.6%–24.2% in soil bulk density, while it increased significantly by 12.8%–34.0% in total porosity and by 43.5%–146.4% in macroporosity at a depth of 5–10 cm. In comparison to the NTS treatment, the adoption of PTS was found to decrease significantly by 10.7%–30.5% soil bulk density, while it increased significantly by 9.9%–42.7% the total porosity and 23.1%–202.8% the macroporosity at a depth of 0–10 cm. Furthermore, the soil microporosity significantly increase of 7.5%–11.1% under the RTS treatment at the 0–5 cm soil depth and 7.7%–11.2% under the PTS treatment at the 10–20 cm soil depth. Soil physical quality index (SQI) significantly increase under the RTS and PTS treatments, with a 41.26% and 57.57% improvement, respectively, in comparison to the NTS treatment. In summary, the adoption of autumn tillage with straw return (RTS and PTS) demonstrated a reduction in soil bulk density, an increase in soil porosity, macroporosity, and a promotion of capillary porosity, and promoted the improvement of soil physical quality on the Eastern Loess Plateau when compared to no-tillage with straw mulch (NTS).